Pengaruh Keselamatan dan Kesehatan Kerja Terhadap Kinerja Pegawai Pada Kantor BPBD Lahat - Kasinem (Jurnal Manajemen dan Bisnis, 2020)
This study aims to see the effect of work safety on employee performance at the Lahat district BPBD office, indicators for the influence of health on employee performance at the Lahat district BPBD office, and the effect of safety and occupational health simultaneously on employee performance at the Lahat district BPBD office. The approach in this research uses descriptive research with a quantitative approach. Using a quantitative approach because the data obtained uses numbers and the analysis uses statistics, the quantitative approach used for research is the population or sample. In determining the sample, the authors took data from the questionnaire results of the Lahat Regency BPBD office employees.The value of safety thit (X1) is 2.037 with a significant level of 0.047 (0.05), rejects H0 and receives H1. This shows that there is a significant influence between Safety (X1) on Employee Performance (Y) at the Lahat Regency BPBD Office. And the Health Value (X2) of 4.567 with a significant level of 0.000 (0.05), rejecting H0 and accepting H1. This shows that there is a significant influence between Occupational Health (X2) on Employee Performance (Y) at the Lahat Regency BPBD Office. The results of the F test were obtained 22,175 by taking a significant level of 5% with a significance level of 0.001 (P-Value <0.05), then H0 was rejected and H1 was accepted. This means that it can be revealed that there is a significant influence between Safety (X1) and Health (X2) together on Employee Performance at the Lahat Regency BPBD Office.